Characterization of technology project management in small and medium-sized enterprises (2018)
The present study was carried out with the support of the IT Cluster of Norte de Santander, made up of thirty-one (31) companies from the technology industry seeking to describe relevant aspects of Project management practices. The research process of the collection of data supported by the survey carried out by the PMI institute, called "Pulse of the Profession" in which variables of interest are taken into account, such as: the existence of a Project office, level of application of standards and good practices applied, among others. Likewise, the analysis of the information is carried out by consolidating data taken from the selected simple, which in this case are the managers or professionals with experience in managing technology projects of the companies under study. Finally, the project concludes that a mínimum number of IT companies comply with the three elements of success of the projects according to PMI: objectives and proposed bussiness scope, time and initial Budget, inadequate cost estimation, dependence on resources, lack of management practices and changes in the priorities of the organizations are the factors that most influenced Project success rates in SMEs.